Series Summation RKHS-Method Applications for Radio-Physics Problems Simulations - Chumachenko, S.; Hahanov, V.; Melnikova, O. (Elektronika ir Elektrotechnika, 2005)
Reproducing Kernel Hilbert Space (RKHS) Methods for Series Summation that allow analytically to obtain alternative representations for series in the finite form are considered. The new mathematical results of the series theory are used. The paper demonstrates the new results which develop theoretical statements of Series Summation Method in RKHS and application to the some radio-physics problems solving. Bibl. 9 (in English; summaries in Lithuanian, English and Russian).